State symbols (image) of the Khiva Khanate and their expression in economic development (Eurasian Journal of History, Geography and Economics, 2026)
The Khiva Khanate, which ruled from 1511 to 1920, has a four-century history. The Khiva Khanate was ruled by two successive dynasties. The state called the Khiva Khanate was actually called the Khorezm State or the Khorezm Khanate. The state symbols (emblems) of the independent Khiva Khanate are among the means of strengthening power, expressing centralized control and ensuring stability in society. In particular, in the case of the Khiva Khanate, it can be observed that through state symbols, the legitimacy of rule, the unity of religion and state, as well as the development of certain principles of economic and cultural life, developed.